Clinical application of asparaginase activity levels following treatment with pegaspargase. Issue 6 (12th November 2014) - Bleyer, Archie; Asselin, Barbara L.; Koontz, Susannah E.; Hunger, Stephen P.
<x xml:space="preserve">Abstract</x> Asparaginase, an enzyme used to treat acute lymphoblastic leukemia and related forms of nonHodgkin lymphoma, depletes asparagine, which leads to lymphoblast cell death. Unlike most chemotherapeutic agents, asparaginase is a foreign protein that can result in clinical allergy and/or silent hypersensitivity with production of neutralizing antibodies that inactivate asparaginase. In North America, asparaginase activity levels can now be obtained via a commercially available assay, for therapeutic drug monitoring and investigation of potential allergic reactions. Herein, we provide recommendations and a corresponding algorithm for the clinical application of this assay after treatment with pegaspargase to evaluate suspected hypersensitivity reactions and/or silent inactivation. Pediatr Blood Cancer 2015;62:1102–1105. © 2014 Wiley Periodicals, Inc.